External and Sensory Qualities of Brown Laying Hen Eggs Fed Diets Supplemented with Purslane (Portulaca oleracea) Meal Rich in Omega-3 Fatty Acids (Faculty of Animal Science Universitas Brawijaya, 2019)
This study was conducted to evaluate the external physical quality and sensory quality of eggs fed diets added with purslane meal (Portulaca oleraceae) as a source of alpha-linolenic acids. The materials used were Hy-Line Brown laying hen (n= 150 hens, 54 weeks old). The design of the study was a one way classification with five experimental diets. Each diet was replicated five times with five hens for each replication. The diets were formulated by supplementing purslane meal to a basal diet. The levels of purslane meal were 0% (T0), 2% (T1), 4% (T2), 6% (T3), 8% (T4). The diets were given to the hens for 35 days with 7 days of adaptation period. To analyse the external quality of the eggs, a total of 30 eggs (n=6 per dietary treatment) collected at day 33, 34, and 35 were used. The sensory analysis used eggs from day 32. The results of the external quality of eggs showed that the addition of purslane meal (Portulaca oleracea) into the diets of laying hens reaching a level of 8% tended to increase egg weight and did not decrease shell thickness, shell weight, the shape index, and specific gravity (P>0.05). Dietary inclusion of purslane meal up to a level of 8% significantly increased (P<0.01) the preference of egg yolk color while texture, taste, flavor, and overall acceptance were not affected. The conclusion is that purslane meal can be included in the laying hen diets up to a level of 8% without decreasing the external physical quality and the sensory quality of boiled eggs. Diets containing purslane meal increase the preference of egg yolk color due to the increase in yolk color intensity.